Economic Viability of the Viticulture Enterprises: Brief Theoretical Aspect - Balko, Sergei; Dementev, Mikhail; Maidanevych, Petr; Maidanevych, Yuliia; Korolenko, Iuliia; Stankevich , Anastasija (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the research is due to the fact that with with the development of new agronomic techniques and process solutions for viticulture for further processing, a necessity arose to assess the economic viability of the viticulture enterprises that use innovation approaches and ways of improving the methods of such research. The key method of studying this problem is assessing the economic viability of the viticulture enterprises, enabling them to determine the economic effect of growing different varieties of grape plantings in detail, assess various grape varieties by standards of production profitability, and determine the economic viability of the capital investments. The paper presents the primary methods for assessing the economic viability of viticulture enterprises. The economic component is reflected, and the efficiency of new techniques is scientifically grounded. As a result of state-order research, by the end of 2021, new knowledge will be obtained on peculiar features of growing table grapes that are promising for Crimea. The obtained research results will allow making recommendations to farms with industrial plantings and nursery bases for growing grape varieties and clones under study with the subsequent introduction thereof in the scientific-production associations, farm enterprises, and other households with different ownership forms. Proper selection of species and variety composition as well as more uniform use of labor resources and equipment is of great importance in raising the economic viability of the viticulture enterprises. Further investigations will aim at studying the yield capacity as one of the indicators of economic viability of viticulture with the final result—the wine quantity from the vine with due account for the variety range. There will be collected the analytical data of economic parameters of growing the specified table and wine grapes for inclusion in the regulation of measures to prepare “typical process flow charts for viticulture” in modern conditions. The work was performed by state order within the frameworks of the research activity on the subject: “Elaboration of efficient technologies for viticulture depending on the growing area by means of studying the agro-biological economic attributes of new varieties, clones, required sets of equipment, and feasibility study of promising process solutions in Crimean conditions” No. 0833-2019-0021.